Searching for Determinants of Pay or Not to Pay Cash Dividend in Indonesia - Nur, Triasesiarta; Karnen, Kresnohadi Ariyoto (The Indonesian Capital Market Review, 2014)
A dividend decision of a firm is an outcome of various considerations. These considerations differ across time and industry. Based on asymetric information – agency theory thougtht, this study re-examined various variables that have a bearing on the dividend decision of a firm. In addition to examining the impact of corporate fundamentals on dividend policy, the study also analyzed the effect of expropriation trigger variables (family ownership, cash funds, the level of diversification and Related Party Transaction/RPT) on a dividend policy. The results of panel logistic regression indicated that Cash Funds, RPT, Profitability, Size, Growth, Debt and Macroecomics variables are the determinants of the dividend policy for Indonesian listed public companies, observed during 2002 to 2010.